MANAGEMENT OF SEWING TRAINING PROGRAM IN INCREASING THE BASIC COMPETENCE OF TRAINING PARTICIPANTS AT WORK TRAINING CENTERS, KABUPATEN SUBANG - Oktaviani, Nindi Dwi; Hufad, Achmad; Saepudin, Asep (Universitas Pendidikan Indonesia (UPI), 2022)
The management of the training program is one of the success factors of the Subang Regency UPTD BLK in the awarding of the Vocational Training Award (PVA) in 2021. The sewing training program is The training program is in great demand by the community because it has ample job opportunities. This study aims to determine how far the management of sewing training programs can improve the basic competence of training participants at the UPTD BLK Subang Regency. This research uses a descriptive qualitative approach with data collection techniques namely interviews, observation, and documentation. The results of this study obtained that 1) at the planning stage, managers identify needs, develop goals, curricula, strategies, evaluation tools, facilities and training infrastructure with instructors, as well as training financing, 2) at the organizing stage, the manager forms a recruitment team, finance team, facilities and infrastructure team, reporting team, as well as instructors as training implementers, where each team works according to the implementation training schedule, 3) at the implementation stage, instructors provide teaching, guiding, and motivating participants so that they are enthusiastic about participating in the training until the program is finished, then during the training participants are active and have the motivation to learn to increase skills in sewing, then sources and learning media are also in accordance with the needs and can be used properly by training participants, 4) at the evaluation stage, the manager carries out a learning evaluation at the end of the program in the form of questions and practice. in addition, managers also carry out program evaluations to see the effectiveness of the implementation of the program, participants also take a competency test organized by the center to obtain a professional certificate. The result of organizing sewing training is an increase in knowledge, skills, and attitudes that participants feel after attending the training.